PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ULAR TANGGA “SUMBER ENERGI” SISWA KELAS IV SDN PENGADEGAN 07 JAKARTA SELATAN - GABY ESTER; SULISTYANI PUTERI RAMADHANI (Jurnal Ilmiah Pendidikan Guru Sekolah Dasar, 2022)
This development research aims to develop learning media based on snakes and laddersin order to optimize science subjects with theme 9 "Kayanya Negeriku" in the material "Sources of Energy" for fourth-grade students at SDN Pengadegan 07 South Jakarta. The problems raised are based on the lack of instructional media, so teachers are required to be creative in choosing the right learning media for students. The research method adapted to the development model developed by Borg and Gall. The study used the following six steps: (1) potential problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, and (6) product revision. The data collection tools used were: the material expert questionnaire and the media expert questionnaire.The results of the validation of all validators showed a very good assessment, namely from the first validator material expert (V1) with a score percentage of 97.3% (very good) and the second validator material expert (V2) with a score percentage of 89% (very good). Meanwhile, the first validator was a media expert (V1) with a percentage of 90.58% (very good) and the second validator was a media expert (V2) with a score percentage of 87% (very good).